Exploring the Impact of Macroeconomic Factors on Company Financial Performance: Insights into Economic Indicators and Sectoral Heterogeneity - Jefri Fernanda; Rizky Marley; Fauzi Suhendra (Journal on Economics, Management and Business Technology, 2024)
This research investigates the relationship between macroeconomic factors and company financial performance, aiming to provide insights into how changes in broader economic conditions influence firms' profitability, risk exposure, and growth prospects. Drawing upon theoretical frameworks, empirical analyses, and practical implications, the study explores the multifaceted dynamics of the macroeconomic-firm nexus. The analysis considers key macroeconomic variables such as interest rates, inflation rates, GDP growth, unemployment rates, and exchange rates, examining their impact on financial performance indicators including revenue growth, profit margins, return on investment, debt-to-equity ratio, and market valuation measures. Findings reveal significant relationships between macroeconomic factors and firm-level outcomes, highlighting the importance of sectoral heterogeneity, financial market responses, and globalization effects. Practical implications for financial managers, policymakers, and investors are discussed, emphasizing the importance of considering macroeconomic conditions in decision-making processes. Overall, this research contributes to advancing understanding of the macro-financial nexus and provides valuable insights for navigating the complexities of the global economy.